SIG MULTI KRITERIA ANALISIS UNTUK PEMILIHAN LAHAN PARKIR DI KOTA SAMARINDA (GIS MCDA FOR SELECTION OF PARKING AREA IN SAMARINDA CITY) - Agus, Fahrul; MP, Sonny; Hamdani, Hamdani (Prosiding SeNAIK, 2013)
Parking area of a great city is a much-needed facility. This is due to the construction of many large cities cause a reduction in vacant land. Vacant land can be used by the general public for a variety of purposes such as motor vehicle parking. Coupled with the growing number of vehicles that packed the main roads that causing the parking area to be something very expensive. This study aims to apply the technological advances of software Geographic Information Systems (GIS) in order to provide useful recommendations in choosing appropriate parking space for the needs of the urban community. Multicriteria decision analysis with Analytical Hierarchy Process method is used to modelling the system. This research has resulted in the design and prototype Web-based GIS software that contains a decision analysis model for the selection of parking space in Samarinda City. WebSIG software decision support for the selection of parking area is expected to assist the local government in land use planning in Samarinda